Коливність розв'язків лінійних функціонально-різницевих рівнянь другого порядку - Карпенко, О.В.; Кравець, В.І.; Станжицький, О.М. (Український математичний журнал, 2013)
Установлены условия колеблемости решений функционально-разностных и дискретных разностных линейных урав- нений второго порядка в случае, когда решения их дифференциальных аналогов являются колеблющимися на отрезке. We establish conditions required for the oscillation behavior of solutions of linear functional-difference equations and discrete linear difference equations of the second order in the case where the corresponding solutions of their differential analogs are oscillating on a segment.